Spatial Dependency of Eco-Efficiency of Agriculture in São Paulo - Carlos Rosano Peña; Carlo Aleksandr Rosano de Almeida; Evaldo César Cavalcante Rodrigues; André Luiz Marques Serrano (BBR: Brazilian Business Review)
This research presents an eco-efficiency index for the municipalities of São Paulo, indicating how much it would be possible to maximize economic and environmental objectives, taking into account the best practices for the municipalities of this region. In this vein, we used the Data Envelopment Analysis method with directional distance functions based on the classic variables of multiproduct production function and the internalization of two externalities (one positive and one negative). The study also used the tools of exploratory spatial data analysis to verify the spatial autocorrelation and spatial heterogeneity of the calculated index. The results indicate that, on average, the analyzed municipalities are able to expand the production and forested areas by 59% and also to reduce degraded areas and inputs in the same proportion. Spatial analysis demonstrated the existence of spatial heterogeneity and autocorrelation between municipalities and the formation of large clusters. Based on these results, priorities for environmental intervention in the state are defined.